Strategi Coorperative Learning dalam Pembelajaran Bahasa Arab - Al-Kaosari, Muhammad; Komalasari, Ratna; Maujud, Fathul (MODELING: Jurnal Program Studi PGMI, 2025)
This study aims to analyze the application of the Cooperative Learning strategy in Arabic language teaching and its effectiveness in improving students’ understanding, participation, and motivation. The research employs a qualitative approach with a descriptive-analytical method, focusing on literature studies that examine various Cooperative Learning models such as Student Teams Achievement Division (STAD), Make a Match, Cooperative Integrated Reading and Composition (CIRC), and Rotating Trio Exchange (RTE). Data were obtained from books, scientific journals, and previous research discussing the implementation of collaborative learning in Arabic instruction. The results show that Cooperative Learning effectively enhances students’ mastery of vocabulary (mufrad?t), critical thinking, and communication skills. Students become more active and confident in using Arabic through discussion and group activities, while teachers act as facilitators to guide the learning process. Integration with digital media such as Quizizz and Kahoot increases engagement and creates a more enjoyable learning atmosphere. Therefore, Cooperative Learning is an effective and relevant strategy for modern Arabic language education in Indonesia. Abstrak Penelitian ini bertujuan untuk menganalisis penerapan strategi Cooperative Learning dalam pembelajaran bahasa Arab serta menilai efektivitasnya dalam meningkatkan pemahaman, partisipasi, dan motivasi belajar siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis melalui studi pustaka terhadap berbagai model Cooperative Learning seperti Student Teams Achievement Division (STAD), Make a Match, Cooperative Integrated Reading and Composition (CIRC), dan Rotating Trio Exchange (RTE). Data diperoleh dari buku, jurnal ilmiah, serta hasil penelitian terdahulu yang relevan dengan penerapan pembelajaran kolaboratif dalam konteks pendidikan bahasa Arab. Hasil penelitian menunjukkan bahwa strategi Cooperative Learning efektif dalam meningkatkan penguasaan kosakata (mufrad?t), kemampuan berpikir kritis, dan keterampilan komunikasi siswa. Siswa menjadi lebih aktif, percaya diri, dan mampu bekerja sama dalam kelompok, sementara guru berperan sebagai fasilitator yang membimbing proses belajar. Integrasi media digital seperti Quizizz dan Kahoot juga meningkatkan keterlibatan dan menciptakan suasana belajar yang menyenangkan. Dengan demikian, Cooperative Learning merupakan strategi yang efektif dan relevan bagi pembelajaran bahasa Arab modern di Indonesia.Artikel sendiri terdiri dari 3500-7500 kata)